The Reality and the Challenges of the Syrian Women refugees working in the Jordanian Society - Majid AL-Share, Zubaida; Karadsheh, Muneer (Jordan Journal of Social Sciences, 2022)
This study aims to identify the reality and challenges faced by the Syrian women refugees working in the Jordanian society by highlighting the following aspects: knowledge of the living conditions of the working Syrian women refugees, and identifying the main social, cultural, economic, legal and practical challenges facing the Syrian women refugee workers. The descriptive analytical approach that is based on the intentional sampling method was used, and a sample of 120 Syrian women refugees, , working in Irbid governorate, was designed for identification, which was chosen in the intended manner in a snowball-rolling way. The findings showthat Syrian refugee women face economic challenges to a high degree, as well as social, cultural, and legal challenges, and challenges inherent to the work environment in a moderate degree.